PERLINDUNGAN ANAK DAN PERTANGGUNGJAWABAN HUKUM TERHADAP PELAKU KEKERASAN SEKSUAL TERHADAP ANAK (TINJAUAN YURIDIS UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK) - Binaadi Ryanjaya; Rachmat Ihya (JOURNAL OF LAW AND NATION, 2024)
This study aims to investigate and assess the sorts of child protection covered by Law No. 23 of 2002, which has been updated with Law No. 35 of 2014, as well as the legal accountability of sexual assault offenders. Normative research includes the study at hand. The findings of this study indicate that the type of child protection covered by Law No. 23 of 2002, which was amended by Law No. 35 of 2014 concerning child protection, namely special protection for children given to: children in emergency situations; children in conflict with the law; children from minority and isolated groups; children who are economically or sexually exploited; child drug abuse; child victims of pornography; HIV/AIDS in children; physical or psychological harm to children; and children who are victims of other forms of child abuse, The study's findings also demonstrate that those who sexually assault minors are legally responsible. Articles 76D and 76E of Law No. 35 of 2014 Concerning Amendments to Law Number 23 of 2002 Concerning Child Protection, for instance, stipulate that offenders may be sentenced to 5 to 15 years in jail and/or a maximum punishment of IDR 5,000,000,000.00. If a parent, guardian, caregiver for a kid, teacher, or other member of the educational staff additionally commits sexual assault, the punishment is raised by one-third of the original amount.